2016
DOI: 10.3382/ps/pew129
|View full text |Cite
|
Sign up to set email alerts
|

Meat quality of broiler breast fillets with white striping and woody breast muscle myopathies

Abstract: The global poultry industry has been faced with emerging broiler breast meat quality issues including conditions known as white striping (WS, white striations parallel to muscle fibers) and woody breast (WB, hardness of raw fillet). Experiments were conducted to evaluate effects of WS and WB hardness on meat quality traits in broiler breast fillets. In Exp. 1, birds were processed at approximately 9 wk of age and deboned at 4 h postmortem (PM); in Exp. 2, birds were processed at approximately 6 and 9 wk of age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
177
1
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(207 citation statements)
references
References 20 publications
21
177
1
8
Order By: Relevance
“…Our WB fillets also displayed a worse water holding capacity (WHC), as demonstrated by the superior cooking losses (P < 0.01), which contributed to the higher total losses (P < 0.05) observed for this group (Table 3). Such result is in accordance with recent literature data (Tijare et al 2016). Muscles could exhibit a reduced ability to hold water because of the myodegeneration.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Our WB fillets also displayed a worse water holding capacity (WHC), as demonstrated by the superior cooking losses (P < 0.01), which contributed to the higher total losses (P < 0.05) observed for this group (Table 3). Such result is in accordance with recent literature data (Tijare et al 2016). Muscles could exhibit a reduced ability to hold water because of the myodegeneration.…”
Section: Resultssupporting
confidence: 94%
“…The exudate appeared with a prevalence of 43.4% and it was mainly fluid and clear (P < 0.01), whereas pinpoint hemorrhages were present in 30% of the cases and mostly in the upper area. On WB samples the WS condition was present in 90% of the cases, thus confirming the evidence that such myopathies often occur simultaneously (Tijare et al 2016), and it was mainly located in the cranial side of the breast, where the muscle displayed maximum thickness. At histological level, fibres of WB samples were identified for their larger CSA (P < 0.001) and for the higher incidence of giant-type fibres among them (P < 0.01) ( Table 5).…”
Section: Resultssupporting
confidence: 71%
“…Similar results were reported by Tijare et al. () using the MORS technique. Conversely, Soglia et al.…”
Section: Impact Of Wb Ws and Sm On Meat Qualitysupporting
confidence: 91%
“…It is reported that, after storage, the cooking loss of nonmarinated woody breast meat was higher than normal breast meat (Tijare et al ., ). Mazzoni et al .…”
Section: Resultsmentioning
confidence: 97%